1992
DOI: 10.1139/f92-129
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Effects of Brief Air Exposure in Exhaustively Exercised Rainbow Trout (Oncorhynchus mykiss): Implications for "Catch and Release" Fisheries

Abstract: Rainbow trout (Oncorhynchus mykiss) which were air exposed for 60 s after exhaustive exercise initially had a much larger extracellular acidosis than trout which were only exercised. In both groups, however, plasma pH returned to normal by 4 h. Blood lactate concentrations were also greater in the air-exposed fish and continued to increase throughout the experiment. During air exposure, there was retention of carbon dioxide in the blood, and oxygen tension (Po2) and hemoglobin:oxygen carriage (Hb:O2) both fell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
262
4
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 258 publications
(275 citation statements)
references
References 14 publications
6
262
4
3
Order By: Relevance
“…Although the range of baseline and elevated levels vary by study from possible factors such as temperature and genetic differences, results from each study consistently demonstrated that the physiological disturbance increased with the duration of stress or exercise. Handling stress has also been demonstrated to cause significant physiological disruptions (Pickering and Pottinger, 1989;Ferguson and Tufts, 1992), and handling stress during the hook removal process is a concern among researchers examining the response of fish to angling (Cooke et al, 2001). We suggest that the initial slope of increase for levels of plasma cortisol and lactate in extended capture fish following landing and handling stress represents the early stages of a stress response that will continue to increase.…”
Section: Effects Of Angling Durationmentioning
confidence: 89%
See 4 more Smart Citations
“…Although the range of baseline and elevated levels vary by study from possible factors such as temperature and genetic differences, results from each study consistently demonstrated that the physiological disturbance increased with the duration of stress or exercise. Handling stress has also been demonstrated to cause significant physiological disruptions (Pickering and Pottinger, 1989;Ferguson and Tufts, 1992), and handling stress during the hook removal process is a concern among researchers examining the response of fish to angling (Cooke et al, 2001). We suggest that the initial slope of increase for levels of plasma cortisol and lactate in extended capture fish following landing and handling stress represents the early stages of a stress response that will continue to increase.…”
Section: Effects Of Angling Durationmentioning
confidence: 89%
“…Once a fish was hooked, other anglers stopped fishing and assisted with the sampling procedure, thus maintaining similar fishing effort. Handling time (hook removal) began when a fish was netted after landing until the angler removed the hook, and anglers were instructed to keep fish under water during the handling portion of capture to avoid any associated mortality due to air exposure (Bouck and Ball, 1966;Ferguson and Tufts, 1992). Anglers were instructed to land fish as they normally would while fishing recreationally, but not to play fish to exhaustion.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations